KARAKTERISASI TEPUNG TULANG IKAN BELIDA (Chitala sp.) SEBAGAI SUMBER KALSIUM DENGAN METODE HIDROLISIS PROTEIN - Hilman Fadhi Putranto; Andi Noor Asikin; Indrati Kusumaningrum (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Belida (Chitala sp.) bone is one of the waste from amplang processing which not treated properly yet until now. The aim of this study were to determine the best condition of presto processing time and boiling frequency by protein hydrolysis method based on based on highest calcium obtained and to characterize properties of fish bone powder obtained. This study used Completely Randomized Design (CRD) with four treatment and three replications. Observed variable in this study were yield  moisture content, protein content,  fat content, ash content, and calcium content. The condition of treatment were P2R1 (2 hour presto and once boiling), P2R2 (2 hour presto and twice boiling), P3R1 (3 hour presto and once boiling), and P3R2 (3 hour presto and twice boiling). The results showed  the treatment of P3R2 was the best treatment  to obtain highest calcium content of fish bone powder. The properties of belida bone powder that P3R2 obtained were 27.77 %  of yield, 3.12 %  of moisture content, 0.26 % of  protein content,0.91 % of fat content, 88.13% of  ash content, and 30.93 % of calcium content.